An energy function based design of second order sliding modes for Automatic Generation Control*. Issue 1 (July 2017) - Trip, Sebastian; Cucuzzella, Michele; Ferrara, Antonella; Persis, Claudio De
Abstract: This paper proposes a decentralized Second Order Sliding Mode (SOSM) control strategy for Automatic Generation Control (AGC) in power networks, where frequency regulation is achieved, and power flows are controlled towards their desired values. This work considers a power network partitioned into control areas, where each area is modelled by an equivalent generator including second order turbine-governor dynamics, and where the areas are nonlinearly coupled through the power flows. Asymptotic convergence to the desired state is established by constraining the state of the power network on a suitable sliding manifold. This is designed relying on stability considerations made on the basis of an incremental energy (storage) function. Simulation results confirm the effectiveness of the proposed control approach.